Penerapan Prinsip Responsibility to Protect Sebagai Konsep Resolusi Konflik - , Nisa Hasna Nabila ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research entitled \"Application of Responsibility to Protect As Conflict Resolution Concepts\" aims to provide a new concept in the RtoP principle by looking at the application of this principle both in the form of their responsibilities in terms of prevent, react and rebuild as well as of the pillars that are inside as a application form of the conflict resolution concepts which includes peacemaking, peacekeeping, and peace building. Synchronization on contemporary conflict precedent also served to support the value relevance of this research. This research is using two research methods. First, discipline configurative study, in which researcher will interpret based on the theory that rests on the general hypothesis, and summarized hypothesis based on existing theories. Second, the heuristic method-configurative study, researchers will use the term here to find out serving, which will try to find or form a new generalization of the concept of responsibility relating to the application of prevent, react and rebuild and also the pillars in the RtoP principle as the application form the concept of conflict resolution peacemaking, peacekeeping, and peace building. The result of this research shows that in practice the principle of Responsibility to Protect is said to have adapted the concept of conflict resolution described by Johan Galtung proposed as an effort to provide protection for the people and addressing mass atrocity. The forms of conflict resolution concept which includes peacemaking, peacekeeping, and peace building principles applied in RtoP can be seen both as responsibility to prevent, responsibility to react, and the responsibility to rebuild, as well as on the application of the pillars of RtoP.